Discrimination Inside: Non-Discrimination as a Tool of Migrant Integration - Farahat, Anuscheh (American Journal of International Law, 2021)
Migration control does not end at the border. Rather, controlling migration (and migrants) continues inside host countries as migration status is used to stratify benefits and limit rights across social, economic, cultural, and political life. This differentiation typically has exclusionary effects and aggravates structural disadvantages that migrants face. This essay argues that we should use anti-discrimination law to address such practices of differentiation and remedy their detrimental effects. While non-discrimination clauses in international human rights treaties provide a powerful resource to this end, they are currently often interpreted in a restrictive manner. “Differentiation within” includes a variety of measures such as restrictions on migration status that limit the right to work, restrictions on political participation, restrictions on freedom of movement based on migration status, and requirements of cultural adaptatio
Keywords: Migration; Migration Control; Migration Status; Social life; Economics; Politics; Culture